Effectiveness of Bibliotherapy on the Assertiveness of Elementary School Students - Marzieh Ahmadian; Mitra Rastgoumoghadam; Leili Seifi; Mohamad Reza Asadi Yoonesi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Objective: This study aimed to determine the effectiveness of bibliotherapy on the assertiveness of low-assertive elementary school students. Method: The present study is a quasi-experimental pre-test-post-test design with control and follow-up groups. The statistical population for the study consisted of shy female students in the fourth grade of a primary school in Qaen City. The researchers used purposeful sampling to select the sample. An intervention using bibliotherapy was administered to the experimental group over 8 sessions, each involving the reading of a storybook for 45 minutes, twice a week. The control group did not receive any intervention. The researchers employed covariance analysis and repeated measurement to test their hypotheses. Findings: The experimental group improved significantly over the control group during the post-test phase. The results also demonstrated that this improvement was sustained during the follow-up phase. These findings suggest that group bibliotherapy is an effective approach for enhancing and maintaining bold behaviour in children who struggle with this skill. Conclusion: It is crucial to utilize techniques that facilitate communication between children and their therapists, and in this study, story therapy through bibliotherapy was found to provide an opportunity for children to overcome their limitations. The current research utilized the bibliotherapy approach, specifically story therapy, to offer a chance for children lacking courage to address their vulnerabilities. The potential factors contributing to this progress can be identified in the characteristics of story therapy as highlighted by experts.